The impact of the symposia of the Institute for Theological Research (UNISA): 1977–1992 - Landman, Christina (Verbum et ecclesia, 2025)
Established in 1975 at the University of South Africa (UNISA), the Research Institute for Theology and Religion (RITR), formerly known as the Institute for Theological Research (ITR), will commemorate its 50th anniversary in 2025. Among the ITR’s key scholarly contributions and outputs were the annual symposia, of which 16 were held consecutively between 1977 and 1992. Prof Willem Vorster was the Director of the ITS from its establishment in 1975 to his death in 1993. It was under his leadership that these symposia were held. Intradisciplinary and/or interdisciplinary implications: In this article, observations of these 16 symposia are made as to: (1) their relevance in the years leading up to the first democratic elections of South Afria in 1994; (2) the theological-social trends which came to expression by the 154 speakers at the symposia; and (3) their contribution to the national and international religious discourses of the day.